Country Positioning of Migration Flows in Ratings of Global Competitiveness - T. P. Danko; A. S. Vyazovikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article shows results of marketing diagnosing of the migration flow development in 5 more or less developed countries of the world: Russia, the US, Canada, Mexico and Argentine. The authors studied and demonstrated the dependence of these countries on certain factors, which affect the level of population quality of life. Migration provides junction of mineral resources split by continents, countries and regions within countries and means of production with labour, it promotes meeting of population’s needs in jobs, housing, means of subsistence, social and professional mobility, changing social status and other characteristics of people life. By using statistic and comparative methods of research (correlative analysis, forecast, trend modeling) the authors managed to confirm or refute different hypotheses about labour migration development. They studied world ratings of countries by the level of expected life span, GDP per capita, weakness of states, unemployment, innovation development, competitiveness. By using the Russian Federation as an example the authors showed key challenges and advantages of migration flow. On the basis of the research recommendations dealing with improvement of migration climate in the Russian Federation were designed.